Penentuan Kondisi Optimum Pembentukan Natrium Silikat (Na2SiO3) Menggunakan Material Dasar Silika Alam dan Natrium Hidroksida (NaOH) - Illa Ramadhani; Budhi Oktavia; Ananda Putra; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2021)
The purpose of this research are to investigate the effective synthesis of sodium silicate and knowing the optimum conditions of the sodium silicate from its solubility in water. Synthesis of sodium silicate was carried out by first activating silica using 1M HCl. The activated silica is then added with NaOH. Based on XRF analysis, it was found that the sodium silicate synthesis method is more effective at high temperatures. Determination of the optimum conditions was carried out at various concentrations of NaOH (2M, 3M, 4 M, 5M and 6M). Based on the research that has been done, the optimum conditions for sodium silicate were obtained by adding NaOH with a concentration of 4M.